Pengertian Merugikan Keuangan Negara Dalam Tindak Pidana Korupsi - Ginting, Jamin (Pelita Harapan University, 2006)
One of element to be liable of doing a corruption in UU No. 20 Year 2001 about change for UU No. 31 Year 1999 about Eradication of Doing a Corruption is the existence of states finance loss. Congeniality of states finance in practice doing a corruption of rather than only at state finance directly at state-owned corporation but also to and also finance in the form of share at Body ofBUMN which is ruled by Limited Liability rule. State Loss which must be proved also owns the field and perception which different Â each other whether/what verification of doing an injustice of corruption earn with the verification materially or having to in just formal.